Microbial Danger Signals Control Transcriptional Induction of Distinct MHC Class I L Lineage Genes in Atlantic Salmon - Svenning, Steingrim; Gondek-Wyrozemska, Agata T.; van der Wal, Yorick Andreas; Robertsen, Børre; Jensen, Ingvill; Jørgensen, Jorunn B.; Edholm, Eva-Stina (Frontiers in Immunology, 2019)
Antigen processing and presentation by major histocompatibility complex (MHC) molecules is a cornerstone in vertebrate immunity. Like mammals, teleost possess both classical MHC class I and multiple families of divergent MHC class I-like genes. While certain mammalian MHC class I-like molecules have proven to be integral in immune regulation against a broad array of pathogens, the biological relevance of MHC class I-like genes in fish remains elusive. This work focuses on MHC class I-like L lineage genes and reveals unique regulatory patterns of six L lineage genes (Sasa-lia, Sasa-lda, Sasa-lca, Sasa-lga, Sasa-lha and Sasa-lfa) in antimicrobial immunity of Atlantic salmon (Salmo salar L.). Using two distinct challenge models with different kinetics and immune pathologies combined with in vitro stimulation using viral and bacterial TLR ligands, we show that de novo synthesis of L lineage genes is uniquely regulated in response to various microbial stimuli. Prior to the onset of classical MHC class I, lia was rapidly and systemically induced by the single-stranded (ss) RNA virus salmon alpha virus 3 (SAV3) and ssRNA and dsRNA TLR ligands but not in response to challenge with the intracellular bacterium Pisciricettsia salmonis. In contrast lga expression was upregulated in response to both viral and bacterial stimuli. A role for distinct MHC class I-like genes in anti-microbial immunity in salmonids was further substantiated by a marked upregulation of lia and lga gene expression in response to type I IFNa stimulation. Comparably, lha showed no transcriptional induction in response to IFNa stimulation but was strongly induced in response to TLR9 ligands. In sharp contrast, lda showed no response to viral or bacterial challenge. Similarly, no induction of lca, which is predominantly expressed in primary and secondary lymphoid tissues, was observed. Together, these findings suggest that certain Atlantic salmon MHC class I-like genes play important and divergent roles in early anti-microbial response and that their regulation, in response to different activation signals, represent a system for selectively promoting the expression of distinct MHC class I-like genes in response to different types of immune challenges